Kritisk realisme og gudsmøtet - Lilleaasen, Robert 19XX- (Teologisk tidsskrift, 2017)
The article argues that critical realism allows for the inclusion of the religious experience of divine encounters in scientific studies. First, the presumption of ontological realism enables an investigation of the backdrop to religious faith. Second, I interpret religious experiences such as divine encounters as an expression of our epistemological relativism - and therefore, as important for us in order to understand our different perspectives on reality. Third, I argue that an open and dynamic understanding of the divine encounter allows it to enter in to critical assessment.